2021
DOI: 10.48550/arxiv.2102.01697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping stellar surfaces II: An interpretable Gaussian process model for light curves

Rodrigo Luger,
Daniel Foreman-Mackey,
Christina Hedges

Abstract: The use of Gaussian processes (GPs) as models for astronomical time series datasets has recently become almost ubiquitous, given their ease of use and flexibility. GPs excel in particular at marginalization over the stellar signal in cases where the variability due to starspots rotating in and out of view is treated as a nuisance, such as in exoplanet transit modeling. However, these effective models are less useful in cases where the starspot signal is of primary interest since it is not obvious how the param… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This is true even in the absence of measurement error: the mapping from a stellar surface to its rotational light curve is so degenerate that there exist an infinite number of solutions to the inverse problem. This fact has been pointed out recently in different contexts (e.g., Cowan et al 2013;Rauscher et al 2018;Sandford & Kipping 2019;Luger et al 2019;Basri & Shah 2020), but it dates back at least to Russell (1906), who demonstrated it by expanding the surface intensity of a celestial body in terms of spherical harmonics (see Figure 2). Russell (1906) showed that many of the modes comprising the intensity profile of a spherical object are in the null space, the set of surface features that have identically zero effect on the light curve.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…This is true even in the absence of measurement error: the mapping from a stellar surface to its rotational light curve is so degenerate that there exist an infinite number of solutions to the inverse problem. This fact has been pointed out recently in different contexts (e.g., Cowan et al 2013;Rauscher et al 2018;Sandford & Kipping 2019;Luger et al 2019;Basri & Shah 2020), but it dates back at least to Russell (1906), who demonstrated it by expanding the surface intensity of a celestial body in terms of spherical harmonics (see Figure 2). Russell (1906) showed that many of the modes comprising the intensity profile of a spherical object are in the null space, the set of surface features that have identically zero effect on the light curve.…”
Section: Introductionmentioning
confidence: 76%
“…Another important feature of S, which we hinted at above, is that it is exactly zero for all odd-degree modes above l = 1. This is a well-known fact: all odd spherical harmonics other than the dipole are in the null space regardless of inclination (e.g., Luger et al 2019). In other words, these spherical harmonics are perfectly antisymmetric in projection over the unit disk when viewed from any orientation.…”
Section: Dependence On Inclinationmentioning
confidence: 95%
See 2 more Smart Citations
“…Disentangling which of these mechanisms is causing these changes in the light curves is difficult, especially if they are occurring on the same time scale (Basri & Shah 2020). Modeling these light curves with a Gaussian Process model (e.g., using starry; Luger et al 2021) may lend insight into the spot evolution that is occurring and provide a metric that can quantitatively measure such changes in the light curve (e.g., Gordon et al 2021). Investigating this is beyond the scope of this work, but we note this as a point of future exploration.…”
Section: Light-curve Evolutionmentioning
confidence: 99%